Evaluasi Kinerja Crushing Plant di PT X Desa Cipinang, Kecamatan Rumpin, Kabupaten Bogor, Provinsi Jawa Barat - M. Hafizh Eliansyah; Sriyanti (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. With a total area of ± 100 Ha. The purpose of this study is to determine the obstacles that occur during production, to determine the availability and work efficiency of mechanical equipment, and to determine the production tonnage of crushing plant equipment. Processing of andesite minerals at the crushing plant unit of PT X consists of three stages, namely primary crushing using a jaw crusher (Metso C-140), secondary crushing using cone crusher 1 (CMC PCC4A) and tertiary crushing using cone crushers 2 & 3 (NH-400). Data processing activities and research results at PT X consist of field activity procedures, crushing plant work cycles, crushing plant working time, crushing plant productivity, actual conveyor belt calculations, and calculation of conveyor belt production losses. Based on data on human barriers and mechanical devices, the value of mechanical availability is 94.77% and work efficiency is 94.83%. Lossing materials that occur during the processing are divided into 5 stages, namely, primaru crushing = 0.25 tons/hour, secondary crushing = 0.16 tons/hour, teriary crushing = 0.14 tons/hour, sizing 1 = 0.07 tons /hour and sizing 2 = 0.03 ton/hour. Production results of jaw crusher = 384.86 tons/hour, cone crusher 1 = 384.70 tons/hour, cone crusher 2 = 163.37 tons/hour and cone crusher 3 = 163.65 tons/hour. The products produced by this company consist of 6 types of products including split 12, split 23, screening, stone ash, and base course. The results of the crushing plant performance evaluation could not meet the production target of 380 tons/hour with a product production of 377.37 tons/hour. Abstrak. Luas wilayah keseluruhan ± 100 Ha. Tujuan penelitian yaitu mengetahui hambatan-hambatan yang terjadi saat produksi, mengetahui nilai ketersediaan dan efesiensi kerja alat mekanis, lossing materials selama proses produksi dan mengetahui tonase produksi alat crushing plant. Pengolahan bahan galian andesit pada unit crushing plant PT X terdiri dari tiga tahap yaitu primary crushing dengan menggunakan jaw crusher (Metso C-140), secondary crushing menggunakan cone crusher 1 (CMC PCC4A) dan tertiary crushing menggunakan cone crusher 2 &3 (NH-400). Kegiatan pengolahan data dan hasil penelitian pada PT X terdiri prosedur kegiatan lapangan, siklus kerja crushing plant, waktu kerja crushing plant, produktivitas crushing plant, perhitungan belt conveyor secara aktual, dan perhitungan losses produksi belt conveyor. Berdasarkan data hambatan manusia dan alat mekanis didapatkan nilai ketersediaan mekanis 94,77% dan efisiensi kerja sebesar 94,83%. Lossing materials yang terjadi selama proses pengolahan terbagi menjadi 5 tahapan yaitu, primary crushing = 0,25 ton/jam, secondary crushing = 0,16 ton/jam, teriary crushing = 0,14 ton/jam, sizing 1 = 0,07 ton/jam dan sizing 2 = 0,03 ton/jam. Hasil Produksi jaw crusher = 384,86 ton/jam, cone crusher 1 = 384,70 ton/jam, cone crusher 2 = 163,37 ton/jam dan cone crusher 3 = 163,65 ton/jam. Produk yang dihasilkan perusahaan ini terdiri dari 6 jenis produk diantaranya yaitu split 1-2, split 2-3, screening, abu batu, dan base course. Hasil evaluasi kinerja crushing plant tidak dapat memenuhi target produksi sebesar 380 ton/jam dengan produksi produk yang diperoleh sebesar 377,37 ton/jam.